2009
DOI: 10.1002/cbic.200800737
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Alarmone, Guanosine 5′‐Diphosphate 3′‐Diphosphate (ppGpp), Predominantly Binds the β′ Subunit of Plastid‐Encoded Plastid RNA Polymerase in Chloroplasts

Abstract: It's alarming: Bacterial alarmone guanosine 5'-diphosphate 3'-diphosphate (ppGpp), which is a key regulatory molecule that controls the stringent response, also exists in chloroplasts of plant cells. Cross-linking experiments with 6-thioguanosine 5'-diphosphate 3'-diphosphate (6-thioppGpp) and chloroplast RNA polymerase indicate that ppGpp binds the beta' subunit of plastid-encoded plastid RNA polymerase that corresponds to the Escherichia coli beta' subunit. Chloroplasts, which are thought to have originated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 43 publications
1
43
1
Order By: Relevance
“…ppGpp appears to act principally through the inhibition of chloroplast transcription to reduce the quantities of individual transcript available for translation and the total translational capacity of the chloroplast by reducing rRNA and tRNA transcript levels ( Figures 4A and 4C). These results are broadly in agreement with previous in vitro data and a recent study with the phytohormone ABA that suggested a link between RSH gene function and chloroplast gene transcription (Sato et al, 2009;Nomura et al, 2012;Yamburenko et al, 2015). A less extensive study that leads to similar conclusions was also published during the final preparation of this manuscript (Maekawa et al, 2015).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…ppGpp appears to act principally through the inhibition of chloroplast transcription to reduce the quantities of individual transcript available for translation and the total translational capacity of the chloroplast by reducing rRNA and tRNA transcript levels ( Figures 4A and 4C). These results are broadly in agreement with previous in vitro data and a recent study with the phytohormone ABA that suggested a link between RSH gene function and chloroplast gene transcription (Sato et al, 2009;Nomura et al, 2012;Yamburenko et al, 2015). A less extensive study that leads to similar conclusions was also published during the final preparation of this manuscript (Maekawa et al, 2015).…”
Section: Discussionsupporting
confidence: 91%
“…Despite the absence of a homolog of DksA, in vitro studies on chloroplast extracts have shown that ppGpp specifically binds to and inhibits the bacterial-like polymerase encoded by the chloroplast genome (Plastid-Encoded Polymerase [PEP]) (Takahashi et al, 2004;Sato et al, 2009). However, the 50% inhibitory concentrations (IC50s) are rather high (1 mM [Sato et al, 2009]; 2 mM [Takahashi et al, 2004]). Chloroplasts also contain an alternative Nucleus-Encoded Polymerase (NEP), which plays a minor role in green tissues and is not inhibited by ppGpp.…”
Section: Ppgpp Regulates Chloroplast Gene Expression By Reducing Steamentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously shown that the chloroplast translation system is negatively regulated by ppGpp in vitro (12), and others have suggested that chloroplast RNA polymerase is a target of ppGpp by demonstrating a physical interaction between a ppGpp analog and the polymerase (13). It remains unclear, however, whether translation and transcription are primary targets of ppGpp in chloroplasts, given that the estimated inhibitory concentrations for ppGpp of ϳ250 M (12) and Ͼ1 mM (6), respectively, are relatively high.…”
mentioning
confidence: 99%
“…Although the mechanism of ppGpp synthesis is rather poorly understood Tozawa & Nomura, 2011;Tozawa et al, 2007), there is accumulating evidence regarding the function of ppGpp in reorienting cellular metabolism and its physiological consequences, including research into sporulation (Balzer & McLean, 2002;Lemos et al, 2004;Ochi et al, 1981), competence (Inaoka & Ochi, 2002), fruiting body formation (Harris et al, 1998), antibiotic production (Bibb, 2005;Hesketh et al, 2001;Hoyt & Jones, 1999;Inaoka et al, 2003;Ochi, 1987aOchi, , 2007Sun et al, 2001), development of persistence (Dahl et al, 2003;Korch et al, 2003), quorum sensing (Baysse et al, 2005;Harris et al, 1998;van Delden et al, 2001), biofilm formation (Balzer & McLean, 2002), pathogenesis (Erickson et al, 2004;Gaynor et al, 2005;Godfrey et al, 2002;Haralalka et al, 2003;Pizarro-Cerdá & Tedin, 2004;Song et al, 2004) and symbiosis (Moris et al, 2005;Wells & Long, 2002;Zhang et al, 2004). The RNA polymerase is the primary target for ppGpp, as confirmed recently by X-ray crystallographic analysis of an RNA polymerase-ppGpp complex (Artsimovitch et al, 2004;Chatterji et al, 1998;Sato et al, 2009). In Bacillus subtilis, the stringent response is directly elicited by an abrupt decrease in GTP level.…”
Section: Introductionmentioning
confidence: 88%